Pengaruh Modal, Harga, Tenaga Kerja, Luas Lahan, Jumlah Produksi Terhadap Pendapatan Petani Gambir di Nagari Solok Bio-Bio (The Influence of Capital, Price, Labor, Land Area, Production Amount on the Income of Gambir Farmers in Nagari Solok Bio-Bio) - Siregar, Masro; Afrizal, Roni; Nofrianil, Nofrianil (Jurnal Ilmiah Sosio Agribis, 2025)
Harau is one of the sub-districts in Lima Puluh Kota Regency that has significant potential as a center for gambir commodity production, with a total land area of 16,708 hectares and a production volume of 10,823.66 tons. The productivity of gambir agriculture in Harau District is the lowest, which is 0.12 ha/kg. One of the smallest administrative areas (Nagari) in Harau District that experienced a decline in productivity was Nagari Solok Bio-Bio. In this study, the influence of capital factors (X1), price (X2), labor (X3), land area (X4), and production volume (X5) was studied simultaneously and partially on the income of gambir farmers in Nagari Solok Bio-Bio. The methodology used was multiple linear regression analysis and a questionnaire with a Likert scale. Based on the results of the study, the average income of gambir farmers per year in Nagari Solok Bio-Bio was IDR 41,889,095. Based on the results of the study, all independent variables, namely capital, price, labor, land area, and production volume, have a significant influence on the income of gambir farmers, both partially and simultaneously. With an Adjusted R-squared (R²) Coefficient of 0.667, the five factors contributed 66.7% to the variation in farmer income.Keywords: Gambir, Income, Multiple Linear Regression